Injectable hydrogel encapsulating Cu2MnS2 nanoplates for photothermal therapy against breast cancer - Ji-jun Fu; Ming-yue Chen; Jie-xia Li; Jun-hua Zhou; Sheng-nan Xie; Ping Yuan; Bo Tang; Cheng-cheng Liu (Journal of Nanobiotechnology, 2018)
Abstract Background In order to explore the possibility of treating breast cancer by local photo-therapy, a photothermal agents loaded in situ hydrogel was established. In detail, The Cu2MnS2 nanoplates were prepared by one-pot synthesis and, the thermosensitive Pluronic F127 was used as the hydrogel matrix. The Cu2MnS2 nanoplates and the hydrogel were characterized by morphous, particle size, serum stability, photothermal performance upon repeated 808 nm laser irradiation as well as the rheology features. The therapeutic effects of the Cu2MnS2 nanoplates and the hydrogel were evaluated qualitatively and quantitatively in 4T1 mouse breast cancer cells. The retention, photothermal efficacy, therapeutic effects and systemic toxicity of the hydrogel were assessed in tumor bearing mouse model. Results The Cu2MnS2 nanoplates with a diameter of about 35 nm exhibited satisfying serum stability, photo-heat conversion ability and repeated laser exposure stability. The hydrogel encapsulation did not negatively influence the above features of the photothermal agent. The nanoplates loaded in situ hydrogel shows a phase transition at body temperature and, as a result, a long retention in vivo. Conclusions The photothermal agent embedded hydrogel played a promising photothermal therapeutic effects in tumor bearing mouse model with low systemic toxicity after peritumoral administration.